2002
DOI: 10.2337/diabetes.51.9.2817
|View full text |Cite|
|
Sign up to set email alerts
|

Nitrosative Stress, Uric Acid, and Peripheral Nerve Function in Early Type 1 Diabetes

Abstract: The present study was performed to determine whether nitric oxide overproduction is associated with deterioration in peripheral nerve function in type 1 diabetes. We measured peripheral nerve function and biochemical indicators of nitrosative stress annually for 3 years in 37 patients with type 1 diabetes. Plasma nitrite and nitrate (collectively NO x ) were 34.0 ؎ 4.9 mol/l in the control subjects and 52.4 ؎ 5.1, 50.0 ؎ 5.1, and 49.0 ؎ 5.2 in the diabetic patients at the first, second, and third evaluations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
64
2
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 49 publications
9
64
2
3
Order By: Relevance
“…Our results demonstrate that a shortened lag time to ONOO Ϫ production is an independent risk factor for the severity of diabetic PN. This is compatible with the notion that ONOO Ϫ is toxic to the endothelium and perineurium (25). A recent immunohistochemistry study (27) in sural nerve biopsies from patients with different PNs, including that of diabetic origin, showed that N⑀-carboxymethyllysine, a major advanced glycation end product resulting from glycoxidation and lipid peroxidation, was detected in the perineurium as well as epineurial, perineurial, and endoneurial vessels.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results demonstrate that a shortened lag time to ONOO Ϫ production is an independent risk factor for the severity of diabetic PN. This is compatible with the notion that ONOO Ϫ is toxic to the endothelium and perineurium (25). A recent immunohistochemistry study (27) in sural nerve biopsies from patients with different PNs, including that of diabetic origin, showed that N⑀-carboxymethyllysine, a major advanced glycation end product resulting from glycoxidation and lipid peroxidation, was detected in the perineurium as well as epineurial, perineurial, and endoneurial vessels.…”
Section: Discussionsupporting
confidence: 85%
“…Nitrotyrosine, which has been used as an indirect marker of ONOO Ϫ generation, is increased in plasma from type 1 and type 2 diabetic patients (24 -26). In patients with early type 1 diabetes, increased nitrotyrosine levels were associated with a deterioration in composite MNCV in the median, ulnar, and peroneal nerves after 3 years (25). Our results demonstrate that a shortened lag time to ONOO Ϫ production is an independent risk factor for the severity of diabetic PN.…”
Section: Discussionmentioning
confidence: 55%
“…There is an active vasodilative mechanism of skin blood vessels that is dependent on C-fiber nociceptors, which accounts for 75% of their dilative capacity (11), and there is an alternate pathway regulating blood flow that is associated with lipid levels, blood pressure, hematocrit, WBC count, and resistance to the action of insulin in diabetes and the metabolic syndrome. This in- crease in NO production has now been reported by other authors (24) and is thought possibly to be due to an excess of a circulating antagonist (asymmetric dimethylarginine). The suggestion has been made that this unbridled production results in NO reacting with reactive oxygen species (ROS) to form peroxynitrite (ONOO Ϫ ), which is damaging to blood vessel structure and function (25).…”
Section: Statisticssupporting
confidence: 76%
“…Enhanced oxidative stress has been documented in peripheral nerve (4,5,8,(12)(13)(14), dorsal root and sympathetic ganglia (15), and vasculature (16,17) of the peripheral nervous system and has been implicated in neurovascular dysfunction and motor and sensory nerve conduction velocity (MNCV and SNCV) deficits, impaired neurotrophic support, nerve metabolic and signal transduction changes, and morphologic abnormalities characteristic for diabetes (4,5,12,14,16 -20). Evidence for the pathophysiologic role of reactive nitrogen species in PDN is also emerging (16,21).…”
mentioning
confidence: 99%